A long‐term copper exposure in a freshwater ecosystem using lotic mesocosms: Invertebrate community responses. (30th May 2017) - Joachim, Sandrine; Roussel, Hélène; Bonzom, Jean‐Marc; Thybaud, Eric; Mebane, Christopher A.; Van den Brink, Paul; Gauthier, Laury
Abstract: A lotic mesocosm study was carried out in 20‐m‐long channels, under continuous, environmentally realistic concentrations of copper (Cu) in low, medium, and high exposures (nominally 0, 5, 25, and 75 μg L −1 ; average effective concentrations <0.5, 4, 20, and 57 μg L −1 respectively) for 18 mo. Total abundance, taxa richness, and community structure of zooplankton, macroinvertebrates, and emerging insects were severely affected at Cu treatment levels of 25 and 75 μg L −1 . Some taxa were sensitive to Cu, including gastropods such as Lymnaea spp. and Physa sp., crustaceans such as Chydorus sphaericus, Gammarus pulex, and Asellus aquaticus, rotifers such as Mytilina sp. and Trichocerca sp., leeches such as Erpobdella sp., and the emergence of dipteran insects such as Chironomini. Other taxa appeared to be tolerant or favored by indirect effects, as in Chironimidae larvae, the emergence of Orthocladiinae, and the zooplankter Vorticella sp., which increased in the 25 and 75 μg L −1 treatments. After approximately 8 mo of Cu exposure, the macroinvertebrate community in the high treatment was decimated to the point that few organisms could be detected, with moderate effects in the medium treatment, and very slight effects in the low‐Cu treatment. Subsequently, most taxa in the high‐Cu exposure began a gradual and partial recovery. By the end of the study at 18 mo, macroinvertebrate taxa richness was similar to control richness, although overall abundances remained lower than controls. After 18 mo of copper exposure, a no‐observed‐effect concentration at the community level for consumers was set at 5 μg L −1 (4 μg L −1 as average effective concentration), and a lowest‐observed‐effect concentration at 25 μg L −1 (20 μg L −1 as average effective concentration). Environ Toxicol Chem 2017;36:2698–2714. © 2017 SETAC